A Connection of Winter Eurasian Cold Anomaly to the Modulation of Ural Blocking by ENSO. Issue 17 (7th September 2021) - Luo, Binhe; Luo, Dehai; Dai, Aiguo; Simmonds, Ian; Wu, Lixin
Abstract: This study investigates how El Niño‐Southern Oscillation (ENSO) modulates winter cold anomalies over central Eurasia (CE) using reanalysis data during 1950–2019. It is found that ENSO can significantly influence winter air temperature over CE mainly through modulating the strength and location of the cyclonic anomaly of Ural blocking (UB) or long‐lived UB events. A strong (weak) cyclonic anomaly of UB on the southeastern (eastern) side of the Ural Mountains tends to occur over midlatitude (high‐latitude) Eurasia during La Niña (El Niño) winters. Such anomalous circulation leads to a strong (weak) cold anomaly over CE, especially over East Asia, due to enhanced (weakened) cold air advection toward the CE during La Niña (El Niño). The UB‐related cyclonic anomaly in the midlatitude (high latitude) side of Eurasia is shown to be related to weakened (enhanced) eastward extension of strong westerly winds over midlatitude Eurasia during La Niña (El Niño) winters. Plain Language Summary: Observations show that in recent decades a strong cold anomaly appears over Eurasia, especially over central Eurasia (CE). This cold anomaly shows notable variations on interannual, decadal and interdecadal timescales. However, what factors lead to its interannual variations is not well understood. Here we show that El Niño‐Southern Oscillation (ENSO) events can influence Eurasian winter air temperature by modulating the strength and location of the cyclonic anomaly of Ural blocking (UB) or the frequency of long‐lived UB events. A La Niña (El Niño) favors a strong (weak) cyclonic anomaly circulation located in the southeastern (eastern) side of the Ural Mountains in the midlatitudes (high latitudes), which leads to a strong (weak) cold anomaly over CE especially in the low latitude Eurasia (i.e., East Asia) through enhanced (weakened) cold air advection. These new results help us understand the physical cause of the interannual variability of the Eurasian cold anomaly modulated by ENSO. Key Points: This paper examines the causal relationship between the Ural blocking (UB) and Eurasian cold anomaly during the La Niña phase in winter El Niño‐Southern Oscillation plays an important role in the interannual variability of winter cold anomaly over the Eurasia The UB leads to stronger cold anomaly over the Eurasian during the La Niña than El Niño